Exogenous application of selenium on sunflower (Helianthus annuus L.) to enhance drought stress tolerance by morpho-physiological and biochemical adaptations - Ameen, Muaz; Zia, Muhammad Anjum; Najeeb Alawadi, Hussam F.; Naqve, Maria; Mahmood, Athar; Shahzad, Ahamad Naeem; Khan, Bilal Ahmad; Alhammad, Bushra Ahmed; Aljabri, Maha; Seleiman, Mahmoud F. (Frontiers in Plant Science, 2024)
Drought stress poses a significant obstacle to agricultural productivity, particularly in the case of oilseed-crops such as sunflower (Helianthus annuus L.). Selenium (Se) is a fundamental micro-nutrient that has been recognized for its ability to enhance plant resilience in the face of various environmental stresses. The FH-770 sunflower variety was cultivated in pots subjected to three stress levels (100% FC, 75% FC, and 50% FC), four Se application rates (0 ppm, 30 ppm, 60 ppm, and 90 ppm). This research aimed to investigate the effect of exogenously applied Se on morpho-physiological and biochemical attributes of sunflower to improve the drought tolerance. Foliar Se application significantly lowered H2O2 (Hydrogen peroxide; ROS) (20.89%) accumulation that markedly improved glycine betaine (GB) (74.46%), total soluble protein (Pro) (68.63%), improved accumulation of ascorbic acid (AA) (25.51%), total phenolics (TP) (39.34%), flavonoids (Flv) (73.16%) and anthocyanin (Ant) (83.73%) and activity of antioxidant system superoxide dismutase (SOD) (157.63%), peroxidase (POD) (100.20%), catalase (CAT) (49.87%) which ultimately improved the sunflower growth by 36.65% during drought stress. Supplemental Se significantly increased shoot Se content (93.86%) and improved calcium (Ca 2+ ), potassium (K + ) and sodium (Na + ) ions in roots by 36.16%, 42.68%, and 63.40% respectively. Selenium supplements at lower concentrations (60 and 90 ppm) promoted the growth, development, and biochemical attributes of sunflowers in controlled and water deficit circumstances. However, selenium treatment improved photosynthetic efficiency, plant growth, enzymatic activities, osmoregulation, biochemical characteristics, and nutrient balance. The mechanisms and molecular processes through which Se induces these modifications need further investigation to be properly identified.